A high entropy alloy nanopowder and its preparation method and application

By adjusting the elemental composition of high-entropy alloys and using liquid phase reduction method to prepare nanopowders, the problem of difficult to remove dye wastewater and chromium ion wastewater in the prior art is solved, and efficient degradation and recycling of nanopowders are achieved.

CN118064782BActive Publication Date: 2025-02-14NANCHANG UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410053326.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-15
Publication Date
2025-02-14
Estimated Expiration
2044-01-15

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently remove dye wastewater and chromium ion wastewater, and the preparation method of high-entropy alloy nano powder is complex, with a powder particle size greater than 50 μm, and there is a lack of nano powder preparation reports.

Method used

By adjusting the elemental composition of high-entropy alloys, nanopowders are prepared by liquid phase reduction method to obtain high-entropy alloy nanopowders with particle size of 30-130nm, with higher specific surface area and pore structure, which can quickly and efficiently degrade azo Dye wastewater and chromium ion wastewater are separated and recovered through magnetic separation technology.

Benefits of technology

It has achieved rapid and efficient degradation of azo dye wastewater and chromium ion wastewater, has good cyclic degradation performance, and has achieved the recycling of nano powders through magnetic separation technology, solving the problem of raw material recycling in wastewater treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118064782B_ABST
    Figure CN118064782B_ABST
Patent Text Reader

Abstract

The present invention provides a high entropy alloy nanopowder and a preparation method and application thereof, and relates to a high entropy alloy nanomaterial. The high entropy alloy nanopowder provided by the present invention is a FeNiCoCrY alloy, which comprises, in atomic percentage, 15-20% Fe, 35-40% Ni, 15-20% Co, 15-20% Cr and 0.5-1.5% Y. The preparation method comprises the following steps: adjusting the Fe-containing 2+ 、Ni 2+ 、Co 2+ Cr 3+ , Y 3+ After the mixed solution becomes alkaline, a reducing agent is added to stir the reaction, and the mixture is cooled and separated to obtain high entropy alloy nanopowder. By adjusting and combining the high entropy alloy element components and preparing nanopowders based on the liquid phase reduction method, nanopowders with higher specific surface area and pore structure can be more strongly and continuously degraded azo dye wastewater and chromium ion wastewater, while having good cyclic degradation performance, and nanopowders can also be separated and recovered by magnetic separation technology.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to high entropy alloy nano materials, and in particular to a high entropy alloy nano powder and a preparation method and application thereof. Background Art

[0002] In the textile, paper printing, leather, paint, plastic and cosmetic industries, organic synthetic dyes with strong coloring rate, high stability, resistance to biodegradation and resistance to photolysis have been widely used. The resulting problem is the discharge of wastewater containing organic dyes. There are a large number of organic matter in these dye wastewaters, and their chemical oxygen demand can reach tens of thousands of milligrams per liter. When these dye wastewaters enter the aquatic environment, they will not only cause visual pollution, but also reduce the transmittance of natural water bodies, thereby affecting the photosynthesis of aquatic plants, reducing the oxygen content in the water, and affecting the ecological environment of the water. In addition, most organic dyes are extremely mutagenic and carcinogenic, which will pose a serious threat to human health.

[0003] With the development of mining, smelting, chemical, electroplating, electronics, leather and other industries, as well as the unreasonable landfill and stacking of civil solid waste, accidental discharge of heavy metal pollutants and the application of large amounts of fertilizers and pesticides, the problem of heavy metal pollution in water bodies has become increasingly serious. Hexavalent chromium Cr(VI) has significant biological toxicity and is increasingly widely used in the industrial field. The US Environmental Protection Agency has defined Cr(VI) as one of the most toxic pollutants, and its maximum acceptable concentration in drinking water is set at 0.05 mg / L. If it cannot be effectively removed at the source of industrial wastewater discharge, discharge into water bodies will cause serious environmental pollution. Therefore, it is of great significance to study how to efficiently remove Cr from wastewater.

[0004] In recent years, zero-valent nano-iron (nZVI) has attracted widespread attention due to its excellent decolorization effect on dye wastewater. Researchers have developed a zero-valent FeNi alloy nanopowder based on nZVI, and combined the zero-valent FeNi alloy nanopowder with SrFe-MOF magnetic powder to form a core-shell FeNi@SrFe-MOF magnetic powder (FSM). FeNi alloy nanopowder has excellent antioxidant properties, which solves the problem that nZVI powder is easy to oxidize and difficult to preserve. At the same time, SrFe-MOF powder has permanent magnetic properties and relies on magnetic force to combine a large amount of FeNi alloy nanopowder on the porous surface; FSM powder takes into account both permanent magnetic and soft magnetic properties, enhancing the magnetic field recovery and treatment capacity after dispersion in wastewater.

[0005] At the same time, high entropy soft magnetic materials are developing rapidly. They are mainly composed of three ferromagnetic elements, Fe, Co and Ni, and one or more non-ferromagnetic elements are added in trace amounts, such as antiferromagnetic Cr, diamagnetic Cu, Si, Ga, paramagnetic Al, Ti, Mn, Sn and other elements, to improve the magnetic properties and mechanical properties of the alloy, thereby obtaining high entropy soft magnetic materials with excellent comprehensive performance. High entropy alloys are considered to be one of the major breakthroughs in alloying theory in recent decades. They have unique alloy design concepts and significant mixed entropy effects, and have excellent properties that many traditional alloys do not have, making the material have potential application value in many fields. Some literature has begun to focus on the research of high entropy alloys as catalysts, hydrogen precipitation from water electrolysis and water oxidation.

[0006] High entropy alloys have many constituent elements, but the alloy atoms in their microstructures all maintain a zero-valent state, which is very consistent with the requirements of the zero-valent nano-iron-nickel powder for the degradation of wastewater. At the same time, the preparation of high-entropy alloy nanopowders is a difficult problem. At present, high-entropy alloys are prepared by atomization, and the powder particle size is greater than 50μm. There are few reports on the preparation of high-entropy alloy nanopowders. Therefore, exploring a new, simple and effective preparation method has very important practical and production significance. Summary of the invention

[0007] The purpose of the present invention is to provide a high entropy alloy nanopowder and a preparation method and application thereof. By adjusting and combining the high entropy alloy element components and preparing the nanopowder based on a liquid phase reduction method, the nanopowder has a higher specific surface area and pore structure, can more strongly and continuously degrade azo dye wastewater and chromium ion wastewater, and has good cyclic degradation performance. The nanopowder can also be separated and recovered by magnetic separation technology.

[0008] The invention provides a high entropy alloy nano powder, which is a FeNiCoCrY alloy and comprises 15-20% of Fe, 35-40% of Ni, 15-20% of Co, 15-20% of Cr and 0.5-1.5% of Y in atomic percentage.

[0009] The high entropy alloy nanopowder provided by the present invention uses the Co element with stronger soft magnetic properties to replace part of the Ni element, so that the types of alloy elements can be increased while maintaining the soft magnetic properties of the alloy powder. At the same time, the Cr element with strong antioxidant ability is used to replace part of the Fe element, which can promote the valence electron exchange between Fe-Cr. In addition, a trace amount of Y element is added to the alloy. Since the Y element has a strong bonding ability with the O element, the antioxidant ability of the powder can be further improved.

[0010] Optionally, the particle size of the high entropy alloy nanopowder is 30-130 nm, and the high entropy alloy nanopowder includes a composite alloy phase with a particle size of 30 nm and a FeNi3 spherical phase with a particle size of 130 nm.

[0011] Optionally, the pore size of the high entropy alloy nanopowder is 0-160 nm, and the pore size of the high entropy alloy nanopowder includes micropores of 0-5 nm, mesopores of 5-50 nm and macropores of 50-160 nm.

[0012] In a second aspect, the present invention also provides a method for preparing a high entropy alloy nanopowder, comprising the following steps: adjusting the Fe 2+ 、Ni 2+ 、Co 2+ Cr 3+ , Y 3+ After the mixed solution becomes alkaline, a reducing agent is added and stirred for reaction, and the mixture is allowed to stand and cool to separate high entropy alloy nanopowders.

[0013] Optionally, when a reducing agent is added to stir the reaction, the reducing agent includes N2H4.

[0014] Optionally, a reducing agent is added to stir the reaction, and when the reducing agent is N2H4, the molar ratio of the N2H4 to all metal ions in the mixed solution is greater than 2.

[0015] Optionally, a reducing agent is added for stirring reaction, and when the reducing agent is N2H4, the pH of the mixed solution is 13, and when the reducing agent is added for stirring reaction, the reaction temperature is controlled to be 80°C, and the stirring reaction time is controlled to be 30-40min.

[0016] In a third aspect, the present invention also provides an application of high entropy alloy nanopowder in the degradation of azo wastewater and chromium ion wastewater, comprising the following steps: adding the high entropy alloy nanopowder to the azo wastewater or chromium ion wastewater, stirring the reaction for 1-3 minutes, and then magnetically separating and recovering the high entropy alloy nanopowder. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 The SEM characterization image and EDS characterization image of the high entropy alloy nanopowder prepared in Example 1 of the present invention;

[0018] Figure 2 This is a surface element distribution diagram of the high entropy alloy nanopowder prepared in Example 1 of the present invention;

[0019] Figure 3 This is an XRD characterization diagram of the high entropy alloy nanopowder prepared in Example 1 of the present invention;

[0020] Figure 4 This is an XPS characterization diagram of the high entropy alloy nanopowder prepared in Example 1 of the present invention;

[0021] Figure 5 This is a BET characterization diagram of the high entropy alloy nanopowder prepared in Example 1 of the present invention;

[0022] Figure 6 This is a DSC characterization graph of the high entropy alloy nanopowder prepared in Example 1 of the present invention;

[0023] Figure 7 The ultraviolet-visible absorption spectrum of the high entropy alloy nanopowder prepared in Example 1 of the present invention when the Congo red solution is subjected to a cyclic degradation test;

[0024] Figure 8 A bar graph showing the degradation efficiency changes of the high entropy alloy nanopowder prepared in Example 1 of the present invention when a cyclic degradation test is performed on a Congo red solution;

[0025] Fig. 9 This is a UV-visible absorption spectrum of the high entropy alloy nanopowder prepared in Example 1 of the present invention when conducting a cyclic degradation test on chromium ion wastewater;

[0026] Fig.10 A bar graph showing the degradation efficiency changes of the high entropy alloy nanopowder prepared in Example 1 of the present invention when a cyclic degradation test is performed on chromium ion wastewater;

[0027] Fig.11 The SEM characterization image of the high entropy alloy nanopowder after the high entropy alloy nanopowder prepared in Example 1 of the present invention is degraded by Congo red solution 100 times;

[0028] Fig.12 This is a SEM characterization image of the high entropy alloy nanopowder after the high entropy alloy nanopowder prepared in Example 1 of the present invention degrades chromium ion wastewater 8 times;

[0029] Fig.13 This is an XPS characterization diagram of the high entropy alloy nanopowder after the high entropy alloy nanopowder prepared in Example 1 of the present invention degrades the Congo red solution;

[0030] Fig.14 This is an XPS characterization diagram of the high entropy alloy nanopowder after the high entropy alloy nanopowder prepared in Example 1 of the present invention degrades chromium ion wastewater;

[0031] Fig.15 It is a magnetic saturation curve Ms diagram of the high entropy alloy nanopowder prepared in Example 1 of the present invention;

[0032] Fig.16 XRD diagrams of the high entropy alloy nanopowder prepared in Example 1 of the present invention before and after degradation of Congo red solution and chromium ion wastewater;

[0033] Fig.17 This is the UV-visible absorption spectrum of the high entropy alloy nanopowder prepared in Example 1 of the present invention when it is treated with a Congo red solution after being analyzed. DETAILED DESCRIPTION

[0034] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Unless otherwise defined, the technical terms or scientific terms used herein should be understood by people with general skills in the field to which the present invention belongs. "Including" and similar words used in this article mean that the elements or objects appearing before the word include the elements or objects listed after the word and their equivalents, without excluding other elements or objects.

[0035] The embodiment of the present invention provides a high entropy alloy nanopowder. In fact, the high entropy alloy nanopowder is a FeNiCoCrY alloy, which includes 15-20% Fe, 35-40% Ni, 15-20% Co, 15-20% Cr and 0.5-1.5% Y in atomic percentage.

[0036] Specifically, when designing the alloy composition, the Co element with stronger soft magnetic properties is used to replace part of the Ni element, so that the types of alloy elements can be increased while maintaining the soft magnetic properties of the alloy powder. At the same time, the Cr element with strong antioxidant ability is used to replace part of the Fe element, which can promote the valence electron exchange between Fe-Cr, and a trace amount of Y element is added to the alloy. Since the Y element has a strong bonding ability with the O element, the antioxidant ability of the powder can be further improved.

[0037] In fact, the present invention also provides a method for preparing high entropy alloy nanopowders. When the powder is prepared based on the liquid phase reduction method, alloy powders with smaller particle sizes can be obtained. Specifically, the method comprises the following steps: adjusting the Fe 2+ 、Ni 2+ 、Co 2+ Cr 3+ , Y 3+ After the mixed solution becomes alkaline, a reducing agent is added and stirred for reaction, and the mixture is allowed to stand and cool to separate high entropy alloy nanopowders.

[0038] In some embodiments, Fe 2+ 、Ni 2+ 、Co 2+ Cr 3+ , Y 3+Specifically, FeSO4, NiSO4, CoCl2, CrCl3, and YCl3 can be dissolved in the mixed solution; in fact, when preparing the mixed solution, the hydrates of the aforementioned metal compounds can be dissolved in deionized water, such as FeSO4·7H2O, NiSO4·6H2O, CoCl2·6H2O, CrCl3·6H2O, and YCl3·6H2O.

[0039] In some embodiments, Fe 2+ 、Ni 2+ 、Co 2+ Cr 3+ , Y 3+ In the mixed solution, Fe 2+ 、Ni 2+ 、Co 2+ Cr 3+ , Y 3+ The molar ratio of Fe in the mixed solution is equivalent to the atomic ratio of Fe, Ni, Co, Cr, and Y in the preset high entropy alloy nanopowder. 2+ 、Ni 2+ 、Co 2+ Cr 3+ , Y 3+ The molar ratio can be 19.5:40:19.5:19.5:1.5.

[0040] In some embodiments, when preparing the mixed solution, the metal compound can be added into deionized water at 80° C. and stirred to dissolve.

[0041] In some embodiments, when adjusting the mixed solution to be alkaline, a NaOH solution may be added to the mixed solution, and the pH of the mixed solution is adjusted to 13.

[0042] In fact, when NaOH solution is added to the mixed solution, the metal ions will combine with hydroxide in the mixed solution to generate corresponding hydroxides, such as Fe(OH)2, Ni(OH)2, Co(OH)2, Cr(OH)3, and Y(OH)3.

[0043] In some embodiments, when a reducing agent is added and stirred for reaction, the reducing agent includes N2H4. In fact, N2H4 can be stirred and reacted with the mixed solution in the form of a solution. Specifically, the molar ratio of the added N2H4 to the metal ions in the mixed solution is greater than 2, that is, n(N2H4) / n(Fe 2+ +Ni 2+ +Co 2+ +Cr 3+ +Y 3+ )>2.

[0044] In some embodiments, when N2H4 is added and stirred for reaction, the pH of the mixed solution is controlled to be 13, the reaction temperature is controlled to be 80°C, and the stirring reaction time is controlled to be 30-40 min.

[0045] In fact, when N2H4 is added and stirred, the following reaction occurs between N2H4 and metal ions in the mixed solution:

[0046] mxD 2+ +6N2H4·H2O+sFe 2+ →[Ni m (N2H4)6Fe s ] (2ms) ++6H2O

[0047] ai 3+ +6N2H4·H2O+sFe 2+ →[Cr a (N2H4)6Fe s ] (2s+3a)+ +6H2O

[0048] bCo 2+ +6N2H4·H2O+sFe 2+ →[Co b (N2H4)6Fe s ] (2bs)+ +6H2O

[0049] mxD 2+ +6N2H4·H2O+aCr 3+ →[Ni m (N2H4)6Cr a ] (2m+3a)+ +6H2O

[0050] mxD 2+ +6N2H4·H2O+nY 3+ →[Ni m (N2H4)6Y n ] (2m+3n)+ +6H2O

[0051] bCo 2+ +6N2H4·H2O+nY 3+ →[Co b (N2H4)6Y n ] (2b+3n)+ +6H2O

[0052] mxD 2+ +6N2H4·H2O+aCr 3+ +sFe 2+ →[Ni m (N2H4)6Cra Fe s ] (2ms+3a)+ +6H2O

[0053] 2[Ni m (N2H4)6Fe s ] (2ms)+ +(4ms)OH - →

[0054] 2Ni m Fe s +(ms)N2↑+(4ms)H2O+(12-ms)N2H4

[0055] 4[Cr a (N2H4)6Fe s ] (2s+3a)+ +(8s+12a)OH - →

[0056] 4Cr a Fe s +(2s+3a)N2↑+(8s+12a)H2O+(24-2s-3a)N2H4

[0057] 2[Co b (N2H4)6Fe s ] (2bs)+ +(4ms)OH - →

[0058] 2Co b Fe s +(bs)N2↑+(4bs)H2O+(12-bs)N2H4

[0059] 4[Ni m (N2H4)6Cr a ] (2m+3a)+ +(8m+12a)OH - →

[0060] 4Ni m Cr a +(2m+3a)N2↑+(8m+12a)H2O+(24-2m-3a)N2H4

[0061] 4[Ni m (N2H4)6Y n ] (2m+3n)+ +(8m+12n)OH - →

[0062] 4Ni m Y n+(2m+3n)N2↑+(8m+12n)H2O+(24-2m-3n)N2H4

[0063] 4[Co b (N2H4)6Y n ] (2b+3n)+ +(8b+12n)OH - →

[0064] 4Co b Y n +(2b+3n)N2↑+(8b+12n)H2O+(24-2b-3n)N2H4

[0065] 4[Ni m (N2H4)6Cr a Fe s ] (2ms+3a)+ +(8ms+12a)OH - →

[0066] 4Ni m Cr a Fe s +(2ms+3a)N2↑+(8ms+12a)H2O+(24-2ms-3a)N2H4.

[0067] In fact, the high entropy alloy nano powder prepared by the preparation method of the high entropy alloy nano powder provided by the present invention has a particle size of 30-130nm, and includes a composite alloy phase with a particle size of 30nm and a FeNi3 spherical phase with a particle size of 130nm; at the same time, its pore size is 0-160nm, and includes micropores of 0-5nm, mesopores of 5-50nm and macropores of 50-160nm. Therefore, the high entropy alloy nano powder provided by the present invention has extremely high surface energy, and this structure is conducive to the diffusion of molecules or ions, so as to facilitate the interaction of the powder with azo wastewater and chromium ion wastewater, thereby achieving the purpose of rapid and efficient degradation.

[0068] In fact, the high entropy alloy nanopowder provided by the present invention has a simple solid solution structure, but the atoms on each lattice point are occupied by atoms of different constituent elements. Due to the size differences and serious lattice distortion between the atoms of each element, the atoms on the lattice points deviate from their respective equilibrium positions, and the system free energy is relatively high. This atomic arrangement that deviates from the equilibrium position is more conducive to the combination of surface atoms and solvent atoms, thereby causing a reduction reaction.

[0069] The present invention also provides an application of high entropy alloy nanopowder in the degradation of azo wastewater and chromium ion wastewater. Specifically, the process comprises the following steps: adding high entropy alloy nanopowder to azo wastewater or chromium ion wastewater, stirring and reacting for 1-3 minutes, and then magnetically separating and recovering the high entropy alloy nanopowder. Thus, the high entropy alloy nanopowder provided by the present invention can degrade azo wastewater and chromium ion wastewater quickly and efficiently at room temperature without changing the pH value of the wastewater.

[0070] Therefore, after the high entropy alloy nanopowder is degraded, it can be separated and recovered through magnetic field treatment, which solves the problem of raw material recovery in wastewater treatment without secondary pollution. At the same time, the recovered high entropy alloy nanopowder can also be recycled, which also has a fast and efficient degradation effect.

[0071] In fact, when high entropy alloy nanopowders are added to azo wastewater, they can act as a reducing agent to provide electrons for the degradation reaction of azo dyes in azo wastewater, and the following reactions mainly occur:

[0072] Fe-2e - =Fe 2+ ;

[0073] Fe 2+ -e - =Fe 3+ ;

[0074] Fe 3+ +2H2O=FeOOH+3H + ;

[0075] Ni-2e - =Ni 2+ ;

[0076] Ni 2+ +2H2O=Ni(OH)2+2H + ;

[0077] Cr-3e - =Cr 3+ ;

[0078] 2Cr 3+ +3H2O=Cr2O3+6H + ;

[0079] Co-2e - =Co 2+ ;

[0080] Co 2+ +H2O=CoO+2H + ;

[0081] Y-3e -=Y 3+ ;

[0082] 2Y 3+ +3H2O=Y2O3+6H + ;

[0083] H + +e - =[H];

[0084] RN=NR′+4[H]→R-NH2+R′-NH2;

[0085] RN=NR′+H + +4e - →R-NH2+R′-NH2;

[0086] This shows that Fe, Ni, Cr, Co, and Y can provide a continuous supply of electrons and H+ for the degradation of azo dyes. The multi-metal synergistic effect can produce a large amount of [H]. A large amount of H+ and [H] promote the breaking of azo double bonds (-N=N-), greatly promoting the degradation reaction.

[0087] In fact, when high-entropy alloy nanopowders are added to chromium ion wastewater, zero-valent iron can reduce Cr(VI) to Cr(III) as an electron donor, and many galvanic cells can be formed on FeNi and FeCo alloy nanopowder particles. Electrons are transferred from Fe0 to Ni0 and Co0, and atoms such as Cr0 lose electrons and replenish Fe, promoting the circulation of FeCo and FeNi galvanic cells, generating hydroxides or oxides and providing H+, and then Cr(VI) ions are reduced when receiving electrons. At the same time, Ni and Co atom doping can significantly improve the removal efficiency of Cr(VI), indicating that the introduction of Ni and Co atoms enhances the reactivity of zero-valent iron. Since the galvanic cells formed between the coupled Fe0 and Ni0, Co0 species can promote continuous electron flow, the surface passivation of zero-valent iron can be effectively prevented.

[0088] In addition, when high entropy alloy nanopowders are added to chromium ion wastewater for degradation reaction, the Cr element content on the powder surface will increase, and the following reactions will mainly occur:

[0089] Fe-2e - =Fe 2+ ;

[0090] Fe 2+ -e - =Fe 3+ ;

[0091] Fe 3+ +2H2O=FeOOH+3H + ; <h2 style=";text-align:left;direction:ltr">

[0092] <h2 style=";text-align:left;direction:ltr"> Ni-2e<h2 style=";text-align:left;direction:ltr"> - <h2 style=";text-align:left;direction:ltr"> (Ni)<h2 style=";text-align:left;direction:ltr"> 2+ <h2 style=";text-align:left;direction:ltr"> ;<h2 style=";text-align:left;direction:ltr"> <h2 style=";text-align:left;direction:ltr">

[0093] <h2 style=";text-align:left;direction:ltr"> Ni<h2 style=";text-align:left;direction:ltr"> 2+ <h2 style=";text-align:left;direction:ltr"> +2H2O = Ni(OH)2+2H<h2 style=";text-align:left;direction:ltr"> + <h2 style=";text-align:left;direction:ltr"> ;<h2 style=";text-align:left;direction:ltr"> <h2 style=";text-align:left;direction:ltr">

[0094] <h2 style=";text-align:left;direction:ltr"> Cr-3e<h2 style=";text-align:left;direction:ltr"> - <h2 style=";text-align:left;direction:ltr"> (Cr)<h2 style=";text-align:left;direction:ltr"> 3+ <h2 style=";text-align:left;direction:ltr"> ;<h2 style=";text-align:left;direction:ltr"> <h2 style=";text-align:left;direction:ltr">

[0095] <h2 style=";text-align:left;direction:ltr"> 2Cr<h2 style=";text-align:left;direction:ltr"> 3+ <h2 style=";text-align:left;direction:ltr"> +3H2O = Cr2O3 + 6H<h2 style=";text-align:left;direction:ltr"> + <h2 style=";text-align:left;direction:ltr"> ;<h2 style=";text-align:left;direction:ltr"> <h2 style=";text-align:left;direction:ltr">

[0096] <h2 style=";text-align:left;direction:ltr"> Co-2e<h2 style=";text-align:left;direction:ltr"> - <h2 style=";text-align:left;direction:ltr"> =Co<h2 style=";text-align:left;direction:ltr"> 2+ <h2 style=";text-align:left;direction:ltr"> ;<h2 style=";text-align:left;direction:ltr"> <h2 style=";text-align:left;direction:ltr">

[0097] <h2 style=";text-align:left;direction:ltr"> Co<h2 style=";text-align:left;direction:ltr"> 2+ <h2 style=";text-align:left;direction:ltr"> +H2O=CoO+2H<h2 style=";text-align:left;direction:ltr"> + <h2 style=";text-align:left;direction:ltr"> ;<h2 style=";text-align:left;direction:ltr"> <h2 style=";text-align:left;direction:ltr">

[0098] <h2 style=";text-align:left;direction:ltr"> Y-3e<h2 style=";text-align:left;direction:ltr"> - <h2 style=";text-align:left;direction:ltr"> =Y<h2 style=";text-align:left;direction:ltr"> 3+ <h2 style=";text-align:left;direction:ltr"> ;<h2 style=";text-align:left;direction:ltr"> <h2 style=";text-align:left;direction:ltr">

[0099] <h2 style=";text-align:left;direction:ltr"> 2Y<h2 style=";text-align:left;direction:ltr"> 3+ <h2 style=";text-align:left;direction:ltr"> +3H2O = Y2O3 + 6H<h2 style=";text-align:left;direction:ltr"> + <h2 style=";text-align:left;direction:ltr"> ;<h2 style=";text-align:left;direction:ltr"> <h2 style=";text-align:left;direction:ltr">

[0100] <h2 style=";text-align:left;direction:ltr"> <h2 style=";text-align:left;direction:ltr"> <h2 style=";text-align:left;direction:ltr">

[0101] <h2 style=";text-align:left;direction:ltr"> HCrO4<h2 style=";text-align:left;direction:ltr"> - <h2 style=";text-align:left;direction:ltr"> →H++CrO4<h2 style=";text-align:left;direction:ltr"> 2- <h2 style=";text-align:left;direction:ltr"> ;<h2 style=";text-align:left;direction:ltr"> <h2 style=";text-align:left;direction:ltr">

[0102] <h2 style=";text-align:left;direction:ltr"> 2CrO4<h2 style=";text-align:left;direction:ltr"> 2- <h2 style=";text-align:left;direction:ltr"> +3Fe+16H<h2 style=";text-align:left;direction:ltr"> + <h2 style=";text-align:left;direction:ltr"> →3Fe<h2 style=";text-align:left;direction:ltr"> 2+ <h2 style=";text-align:left;direction:ltr"> +2Cr<h2 style=";text-align:left;direction:ltr"> 3+ <h2 style=";text-align:left;direction:ltr"> +8H2O;<h2 style=";text-align:left;direction:ltr"> <h2 style=";text-align:left;direction:ltr">

[0103] <h2 style=";text-align:left;direction:ltr"> HCrO4<h2 style=";text-align:left;direction:ltr"> - <h2 style=";text-align:left;direction:ltr"> +3Fe<h2 style=";text-align:left;direction:ltr"> 2+ <h2 style=";text-align:left;direction:ltr"> +7H<h2 style=";text-align:left;direction:ltr"> + <h2 style=";text-align:left;direction:ltr"> →3Fe<h2 style=";text-align:left;direction:ltr"> 3+ <h2 style=";text-align:left;direction:ltr"> +Cr<h2 style=";text-align:left;direction:ltr"> 3+ <h2 style=";text-align:left;direction:ltr"> +4H2O;<h2 style=";text-align:left;direction:ltr"> <h2 style=";text-align:left;direction:ltr">

[0104] <h2 style=";text-align:left;direction:ltr"> CrO4<h2 style=";text-align:left;direction:ltr"> 2- <h2 style=";text-align:left;direction:ltr"> +3Fe<h2 style=";text-align:left;direction:ltr"> 2+ <h2 style=";text-align:left;direction:ltr"> +8H<h2 style=";text-align:left;direction:ltr"> + <h2 style=";text-align:left;direction:ltr"> →3Fe<h2 style=";text-align:left;direction:ltr"> 3+ <h2 style=";text-align:left;direction:ltr"> +Cr<h2 style=";text-align:left;direction:ltr"> 3+ <h2 style=";text-align:left;direction:ltr"> +4H2O;<h2 style=";text-align:left;direction:ltr"> <h2 style=";text-align:left;direction:ltr">

[0105] This shows that during the degradation process, only Fe0 is involved in the reaction, and other atoms lose electrons and replenish iron, promoting the circulation of FeCo and FeNi primary batteries, generating hydroxides or oxides and providing H + , which can further promote the reduction of Cr, however, when Fe 3+ After saturation, the degradation of Cr becomes very difficult.

[0106] Example 1

[0107] This embodiment 1 provides a high entropy alloy nanopowder - Fe 19.5 Ni 40 Co 19.5 Cr 19.5 Y 1.5 The preparation method comprises the following steps:

[0108] S1. 19.5 mol of FeSO4·7H2O, 40 mol of NiS04·6H2O, 19.5 mol of CoCl2·6H2O, 19.5 mol of CrCl3·6H2O, and 1.5 mol of YCl3·6H2O were stirred and dissolved in deionized water to prepare a mixed solution;

[0109] S2, adding N2H4 solution to the mixed solution, stirring and reacting for 40 minutes, and then cooling the mixture to obtain an alloy powder suspension. The alloy powder in the suspension was magnetically separated, and then washed with anhydrous ethanol for 3 times and dried to obtain Fe 19.5 Ni 40 Co 19.5 Cr 19.5 Y 1.5 High entropy alloy nanopowders.

[0110] Performance Test:

[0111] Congo red degradation test: 1 g of the high entropy alloy nanopowder prepared in Example 1 was put into 10 mL of a 250 mg / L Congo red solution. After stirring for 1 min, 2 mL of the degraded water sample was taken using a pipette and placed in a quartz reaction cup with an optical path of 10 mm. The absorbance of the water sample was tested at 200 nm-800 nm using a UV-visible photometer with a scanning rate of 120 nm / min. Figure 7 The degradation efficiency of Congo red by high entropy alloy nanopowder was calculated. The test was repeated three times and the average degradation efficiency was calculated. The results are shown in Figure 8 shown.

[0112] Congo red degradation cycle performance test: 1g of the high entropy alloy nanopowder prepared in Example 1 was subjected to a continuous cycle degradation test on 10mL of a 250mg / L Congo red solution. After one degradation was completed, the filtered high entropy alloy nanopowder was directly put into the next degradation process; the water samples after the 11th, 21st, 31st, 41st, 51st, 61st, 71st, 81st, 91st and 100th degradation were subjected to absorbance tests. Figure 7 As shown, the average degradation efficiency of high entropy alloy nanopowder to Congo red at the 11th, 21st, 31st, 41st, 51st, 61st, 71st, 81st, 91st and 100th times is calculated, as shown in Figure 8 As shown; SEM characterization of the high entropy alloy nanopowder that completed the 100th Congo red solution continuous degradation test is shown as Fig.11 XPS characterization was performed as shown Fig.13 shown.

[0113] Chromium ion degradation test: 1 g of the high entropy alloy nanopowder prepared in Example 1 was put into 10 mL of chromium ion wastewater with a concentration of 1.2 g / L. After stirring for 1 min, 2 mL of the degraded water sample was taken using a pipette and placed in a quartz reaction cup with an optical path of 10 mm. The absorbance of the water sample was tested at 200 nm-800 nm using a UV-visible photometer with a scanning rate of 120 nm / min. Fig. 9 The degradation efficiency of high entropy alloy nanopowder on chromium ions was calculated. The test was repeated three times and the average degradation efficiency was calculated. The results are shown in Fig.10 shown.

[0114] Chromium ion degradation cycle performance test: 1g of the high entropy alloy nanopowder prepared in Example 1 was subjected to a cyclic degradation test on 10mL of chromium ion wastewater with a concentration of 1.2g / L; the water samples after the 2nd to 8th degradation were subjected to absorbance tests such as Fig. 9 As shown, the average degradation efficiency of chromium ions by high entropy alloy nanopowders for the 2nd to 8th times is calculated as follows Fig.10 As shown; SEM characterization of the high entropy alloy nanopowder that completed the 8th chromium ion wastewater continuous degradation test is shown as Fig.12 XPS characterization was performed as shown Fig.14 shown.

[0115] High entropy alloy nanopowder soft magnetic properties test: The high entropy alloy nanopowder prepared in Example 1 was tested for soft magnetic properties. The results are as follows: Fig.15 As shown, the outer wall of the container used for chromium ion wastewater degradation is adsorbed by a magnet, and the state position of the high entropy alloy nanopowder in the container is observed as shown in Fig.15 As shown in the illustration.

[0116] Cyclic degradation performance test of high entropy alloy nanopowders: After the high entropy alloy nanopowders that have completed the 100th continuous cyclic degradation of Congo red solution are analyzed using NaOH ethanol solution as the analytical solution, the analyzed high entropy alloy nanopowders are cyclically subjected to degradation tests on Congo red solution. The results are as follows: Fig.17 shown.

[0117] Morphological characterization:

[0118] The microstructure of the surface of the high entropy alloy nanopowder prepared in Example 1 was observed by a scanning electron microscope (SEM, Scios2, CZ). Figure 1 , 2 As shown; the phase composition of the surface of the high entropy alloy nanopowder prepared in Example 1 was detected by X-ray diffraction (XRD, D8ADVANCE, Bruker, USA), as shown Figure 3 As shown; the high entropy alloy nanopowder prepared in Example 1 was characterized by XPS. Figure 4 As shown; the high entropy alloy nanopowder prepared in Example 1 was characterized by BET. Figure 5 As shown; the DSC characterization of the high entropy alloy nanopowder prepared in Example 1 is shown in Figure 6 As shown; XRD characterization of high entropy alloy nanopowder before and after degradation of Congo red solution and chromium ion wastewater Fig.16 shown.

[0119] Result analysis:

[0120] from Figure 1 It can be seen from the figure that the high entropy alloy nanopowder is a dual-phase powder consisting of a spherical powder phase with a particle size of about 30nm and a spherical powder phase with a particle size of about 130nm. Figure 2 From the SEM scanning analysis of high entropy alloy nanopowders, it can be seen that the high entropy alloy nanopowders are composed of Fe, Ni, Co, Cr, and Y elements. The powder with a particle size of about 130nm is FeNi3 phase, and the powder with a particle size of about 30nm is an alloy phase composed of multiple alloy elements, such as Figure 3 This is also confirmed by the XRD phase analysis of high entropy alloy nanopowders. Figure 4 From the XPS full spectrum of the high entropy alloy nanopowder shown, it can be seen that Fe, Ni, Co, Cr, and Y elements are present in the high entropy alloy nanopowder.

[0121] from Figure 3It can be seen that the main phase structures of high entropy alloy nanopowders are FeNi3 phase, NiCrFe phase, Co3Fe4 phase, Cr2Ni3 phase, Co2Y phase and Ni2Y phase. Among them, the diffraction peaks of the powder at 2θ=44.2°, 51.5° and 75.8° correspond to the (111), (200) and (220) crystal planes of the FeNi3 phase, respectively; the diffraction peaks of the powder at 2θ=44.6°, 64.9° and 82.3° correspond to the (111), (200) and (220) crystal planes of the NiCrFe phase, respectively; the diffraction peaks of the powder at 2θ=44.6°, 65.0° and 82.3° correspond to the (110), (200) and (211) crystal planes of the CrFe4 phase, respectively: the diffraction peaks of the powder at 2θ=44.7°, 65.1° and 82.4° correspond to the (111), (200) and (211) crystal planes of the Co3Fe7 phase, respectively; The diffraction peaks at 2θ=43.7°, 51.0° and 75.0° correspond to the (111), (200) and (220) crystal planes of Cr2Ni3 phase, respectively; the diffraction peaks of the powder at 2θ=35.4°, 43.7° and 67.7° correspond to the (220), (222) and (511) crystal planes of Co2Y phase, respectively; the diffraction peaks of the powder at 2θ=30.9°, 37.2°, 43.7° and 49.1° correspond to the (101), (110), (111) and (201) crystal planes of Co5Y phase, respectively; the diffraction peaks of the powder at 2θ=35.4°, 43.8° and 67.9° correspond to the (220), (222) and (511) crystal planes of Ni2Y phase, respectively.

[0122] from Figure 5 It can be seen from the N2 adsorption-desorption isotherm and pore size distribution (PSD) curve of the high entropy alloy nanopowder that the specific surface area of ​​the high entropy alloy nanopowder is 136.23 m 2 / g, BJH mesopore desorption pore size (average mesopore size) is 6.12nm, showing typical IV type characteristics, and H1 type hysteresis loop appears, and its area is mainly concentrated in the higher relative pressure range of 0.43-0.99 (p / p0). From the pore size distribution (PSD) curve, it can be seen that the pore size of the high entropy alloy nanopowder is mainly concentrated between 0-160nm, the micropore pore size is mainly distributed in 1.27nm, the mesopore pore size is mainly distributed in 5.04nm, 23.4nm, 34.33nm, and the macropore pore size is mainly distributed in 50.4nm, 68.5nm, 86.24nm and 117.23nm. Therefore, it can be explained that the high entropy alloy nanopowder prepared by the present invention has a porous hierarchical structure of micropores-mesopores-macroporous, and has extremely high surface energy, which is conducive to the diffusion of adsorbed molecules or ions.

[0123] from Figure 6From the DSC curve of the medium-high entropy alloy nanopowder, it can be seen that the thermal decomposition process of the high entropy alloy nanopowder is mainly three extremes: an obvious endothermic absorption peak appears at 100°C, which indicates that the powder begins to crystallize, and thus the specific gravity decreases significantly; the loss peak is reached at 450°C, and the crystallization ends; the powder begins to undergo phase change from 450-550°C, and the specific gravity of the powder remains unchanged; a small exothermic absorption peak appears at 550°C, which indicates that the phase change of the powder ends, and the specific gravity continues to decrease slowly. This shows that the high entropy alloy nanopowder prepared by the present invention has good thermal stability.

[0124] from Figure 7 It can be seen that after the high entropy alloy nanopowder prepared in Example 1 is added to the Congo red solution, the absorbance of Congo red decreases immediately after stirring for 1 minute, and its characteristic absorption peak λ=497nm disappears, and the absorbance curve has become smooth. Therefore, it can be considered that after the addition of the high entropy alloy nanopowder, the Congo red in the Congo red solution has been removed, which shows that the high entropy alloy nanopowder provided by the present invention has an efficient and rapid removal effect on Congo red. In addition, from Figure 7 and Figure 8 It can be seen that the high entropy alloy nanopowder provided by the present invention has good cycle performance. When the Congo red solution is subjected to 100 cycles of degradation, it still has a good removal effect. Even after 100 cycles, the removal rate of Congo red is still 100%.

[0125] from Fig. 9 It can be seen that after the high entropy alloy nanopowder prepared in Example 1 is added to the chromium ion wastewater, the absorption peak of Cr(IV) at 315nm disappears, which shows that the high entropy alloy nanopowder can have a significant removal effect on chromium ions, and Fig. 9 The UV-visible absorption spectra of the 7th and 8th cycle tests show that the absorption peak at 315nm is significantly enhanced. Fig. 9 The degradation solutions corresponding to the 7th and 8th cycles in the illustration are light green; Fig.10 It can be seen that when the high entropy alloy nanopowder was subjected to 8 continuous cycle tests on chromium ion wastewater, the removal efficiency of Cr(IV) was 100%, 100%, 99%, 99%, 98%, 100%, 93% and 81% respectively.

[0126] from Fig.11 It can be seen that after the high entropy alloy nanopowder was used to degrade Congo red, the morphology of the high entropy alloy nanopowder itself did not change, but S, N, and Na elements were added on its surface, which shows that Congo red was successfully degraded by the high entropy alloy nanopowder, and related substances remained on the surface of the powder.

[0127] from Fig.12It can be seen that after the high entropy alloy nanopowder removes Cr(IV), the morphology of the high entropy alloy nanopowder itself does not change, but the Cr element content on its surface increases.

[0128] from Fig.13 It can be seen from the figure that when high entropy alloy nanopowders are used to degrade Congo red, all elements in the high entropy alloy nanopowders participate in the degradation reaction, and the valence state changes from zero to two or three valences. Fig.13 From the XPS spectrum of Fe2p in A, it can be seen that the fitting peaks at 710.15, 711.15, 712.05, 713.15, and 714.25 eV all belong to the main peak of 2p3 / 2 of FeOOH, which indicates that the surface of the degraded high entropy alloy nanopowder has an oxide layer in the form of FeOOH; Fig.13 From the XPS spectrum of Ni2p in B, it can be seen that the fitting peaks at 856.32, 873.9, 862.13, and 879.89 eV belong to the main peaks and satellite peaks of 2p3 / 2 and 2p1 / 2 of Ni(OH)2, respectively; Fig.13 From the XPS spectrum of Co2p in C, it can be seen that the fitting peaks at 780.96, 783.06, 786.46, and 787.42 eV are all attributed to the main peak of 2p3 / 2 of CoO; Fig.13 From the XPS spectrum of Cr2p in D, it can be seen that the fitting peaks at 576.5, 577.51, 578.29, 579.29, and 579.7 eV are all attributed to the main peak of 2p3 / 2 of Cr2O3; Fig.13 From the XPS spectrum of Y3d in E, it can be seen that there is a strong energy loss peak at 168.2eV, and the fitting peaks at 158.03 and 160.83eV are respectively attributed to the main peaks of 3d5 / 2 and 3d3 / 2 of Y2(CO3)3. Among them, the formation of Y2(CO3)3 is mainly produced by the reaction of Y oxide with CO2 in the air; Fig.13 From the XPS spectrum of O1s in F, it can be seen that the fitting peak at 529.80 eV belongs to the lattice oxygen of MO, the fitting peak at 531.53 eV belongs to the lattice oxygen of MO and the O atom of M-OH, and the fitting peak at 532.86 eV belongs to organic matter or SO4 2 -O atom.

[0129] from Fig.14 From the XPS spectrum of Fe2p in A, it can be seen that the fitting peaks at 709.87, 710.87, 711.79, 712.89, and 713.99 eV are all attributed to the main peak of 2p3 / 2 of FeOOH; Fig.14From the XPS spectrum of Ni2p in B, it can be seen that the fitting peaks at 856.07, 873.56, 862.83, and 879.64 eV belong to the main peaks and satellite peaks of 2p3 / 2 and 2p1 / 2 of Ni(OH)2, respectively; Fig.14 From the XPS spectrum of Co2p in C, it can be seen that the fitting peaks at 780.72, 782.82, 786.22, and 787.22 eV are all attributed to the main peak of 2p3 / 2 of CoO; Fig.14 From the XPS spectrum of Cr2p in D, it can be seen that the fitting peaks at 576.19, 577.20, 577.98, 578.98, and 579.39 eV are all attributed to the main peak of 2p3 / 2 of Cr2O3. After 8 consecutive cycles, Cr(VI) is reduced to Cr(III) and exists in the form of Cr2O3. Fig.14 From the XPS spectrum of Y3d in E, it can be seen that the fitting peaks at 157.83 and 159.83 eV belong to the main peaks of 3d5 / 2 and 3d3 / 2 of Y2(CO3)3, respectively, and a strong energy loss peak appears at 168.2 eV; Fig.14 The XPS spectrum of O1s in F shows that O is indeed involved in the degradation reaction. The fitting peak at 529.59 eV belongs to the lattice oxygen of MO, the fitting peak at 531.26 eV belongs to the lattice oxygen of MO and the O atom of M-OH, and the fitting peak at 532.58 eV belongs to SO4 2- of O atoms.

[0130] from Fig.15 It can be seen that the high entropy alloy nanopowder provided by the present invention has good soft magnetic properties, and its saturation magnetization intensity Ms is 17.3emu / g. When the high entropy alloy nanopowder is used to perform a magnetic separation experiment on wastewater, after a magnet is placed on the outer wall of the wastewater container, the high entropy alloy nanopowder will be quickly adsorbed to the inner wall of the container, thereby facilitating the separation of the treated wastewater from the high entropy alloy nanopowder, showing excellent magnetic separation ability.

[0131] from Fig.16 It can be seen that the high entropy alloy nanopowder provided by the present invention has not undergone significant changes in the powder after 100 consecutive cycles of degradation of the Congo red solution or 8 consecutive cycles of degradation of the chromium ion wastewater. Therefore, after the high entropy alloy nanopowder has been subjected to 100 consecutive cycles of degradation of the Congo red solution, the high entropy alloy nanopowder can be analyzed and then put into a new round of degradation process, which is of great significance for the regeneration and reuse of the high entropy alloy nanopowder.

[0132] from Fig.17It can be seen that when the high entropy alloy nanopowder is analyzed after a round of saturated adsorption and then the Congo red solution is recycled and degraded again, it still has the effect of rapid and efficient degradation, and the removal rate of the Congo red solution can basically reach 100%.

[0133] Although the embodiments of the present invention are described in detail above, it is obvious to those skilled in the art that various modifications and variations can be made to these embodiments. However, it should be understood that such modifications and variations are within the scope and spirit of the present invention as described in the claims. Moreover, the present invention described herein may have other embodiments and may be implemented or realized in a variety of ways.

Claims

1. A high entropy alloy nanopowder, characterized in that: The high entropy alloy nanopowder is a FeNiCoCrY alloy, which comprises 15-20% Fe, 35-40% Ni, 15-20% Co, 15-20% Cr and 0.5-1.5% Y in atomic percentage.

2. The high entropy alloy nanopowder according to claim 1, characterized in that: The particle size of the high entropy alloy nanopowder is 30-130nm, and the high entropy alloy nanopowder includes a composite alloy phase with a particle size of 30nm and a FeNi3 spherical phase with a particle size of 130nm.

3. The high entropy alloy nanopowder according to claim 1, characterized in that: The pore size of the high entropy alloy nanopowder is 0-160nm, and the pore size of the high entropy alloy nanopowder includes micropores of 0-5nm, mesopores of 5-50nm and macropores of 50-160nm.

4. A method for preparing a high entropy alloy nanopowder according to any one of claims 1 to 3, characterized in that: The following steps are involved: Adjust the content of Fe 2+ 、Ni 2+ 、Co 2+ Cr 3+ , Y 3+ After the mixed solution becomes alkaline, a reducing agent is added and stirred for reaction, and the mixture is allowed to stand and cool to separate high entropy alloy nanopowders.

5. The preparation method according to claim 4, characterized in that: When a reducing agent is added and the reaction is stirred, the reducing agent includes N2H4.

6. The preparation method according to claim 5, characterized in that: A reducing agent is added to stir the reaction, and when the reducing agent is N2H4, the molar ratio of the N2H4 to all the metal ions in the mixed solution is greater than 2.

7. The preparation method according to claim 5, characterized in that: Add a reducing agent and stir to react. When the reducing agent is N2H4, the pH of the mixed solution is 13. When adding the reducing agent and stirring to react, the reaction temperature is controlled to be 80°C, and the stirring reaction time is controlled to be 30-40 minutes.

8. Use of the high entropy alloy nanopowder as claimed in any one of claims 1 to 3, or the high entropy alloy nanopowder prepared by the preparation method as claimed in any one of claims 4 to 7 in the degradation of azo wastewater and chromium ion wastewater.

9. The use according to claim 8, characterized in that: The following steps are involved: The high entropy alloy nanopowder is added into azo wastewater or chromium ion wastewater, stirred for reaction for 1-3 minutes, and then the high entropy alloy nanopowder is magnetically separated and recovered.

Citation Information

Patent Citations

  • Load-type nano zero-valence iron particle and preparation method therefor

    CN104815982A

  • Zero-valent nanometer iron-nickel powder for treating dyestuff wastewater and preparing method thereof

    CN110394443A